Feasibility of Apatinib in Radioiodine-Refractory Differentiated Thyroid Carcinoma - Du, Wei; Shi, Xiangyu; Fang, Qigen; Zhang, Xu; Liu, Shanting (Frontiers in Endocrinology, 2022)
Objectives Our aim was to describe our experience in using apatinib as treatment for radioiodine-refractory differentiated thyroid carcinoma (RAIR-DTC). Methods Forty-seven patients undergoing apatinib treatment for RAIR-DTC were prospectively enrolled in this study. The study endpoints were objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and rate of adverse events. Results No patients achieved complete response, while 36 (76.6%) and 8 (17.0%) patients achieved partial response and stable disease, respectively. The ORR and DCR were 76.6% and 93.6%, respectively. The median PFS and OS were 18 and 59 months, respectively. A total of 91 adverse events occurred, of which 21 were graded as grade 3 or higher. There were no drug-related deaths. Conclusions Apatinib has distinct anti-RAIR-DTC efficacy in terms of ORR, PFS, and OS and has a favorable safety profile. It is a feasible treatment option for RAIR-DTC.